Mobile robotics : mathematics, models and methods - Kelly, Alonzo (Cambridge University Press, 2013)
"Mobile Robotics offers comprehensive coverage of the essentials of the field suitable for both students and practitioners. Adapted from Alonzo Kelly's graduate and undergraduate courses, the content of the book reflects current approaches to developing effective mobile robots. Professor Kelly adapts principles and techniques from the fields of mathematics, physics and numerical methods to present a consistent framework in a notation that facilitates learning and highlights relationships between topics. This text was developed specifically to be accessible to senior level undergraduates in engineering and computer science, and includes supporting exercises to reinforce the lessons of each section. Practitioners will value Kelly's perspectives on practical applications of these principles. Complex subjects are reduced to implementable algorithms extracted from real systems wherever possible, to enhance the real-world relevance of the text"--Vydavatelská anotace
Keywords: mobilní roboty; roboty; robotika; matematické modely; matematické metody; robots; mobile robots; robotics; mathematical models; mathematical methods; učebnice vysokých škol; textbooks (higher)